Social Determinants and Hypertension Incidence in Productive-Age Adults: A Literature - Keyza Cynthia Putri Priono; Novi Dian Arfiani (Dian Nuswantoro Semarang, 2026)
Hypertension, commonly known as high blood pressure, is a blood disorder characterized by an increase in blood pressure above the normal threshold of 140/90 mmHg during two measurements within a five-minute period in a calm state. Hypertension is one of the non-communicable diseases that causes high mortality rates in various countries. Increased blood pressure puts a heavier workload on the heart in pumping blood and circulating it throughout the body. Therefore, a person with high blood pressure is at high risk of developing serious complications. According to the WHO, most people with hypertension worldwide live in low- and middle-income countries. Although the prevalence of hypertension is greater in older age groups, it does not mean that younger age groups are immune to hypertension. The purpose of this study was to determine the social determinants of health on the incidence of hypertension in productive age groups. This study used a literature review method. This study concluded that the risk factors for hypertension in productive age are lifestyle factors, which include low physical activity, high sodium consumption, low fiber consumption, smoking, and alcohol consumption; psychosocial factors, which include knowledge, attitude, and stress levels; and host factors, which include age, genetics, nutritional status, and history of comorbidities.